Upaya Pengembangan Inovasi Melalui Jaringan Inovasi Pelayanan Publik - Haerana, Haerana; Fatmawati, Fatmawati; Burhanuddin, Burhanuddin; Mustari, Nuryanti (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2022)
The Public Service Innovation Network is a form of cooperation in the development of public service innovations that are run between related agencies, as an effort so that all parties are connected to each other in the development of public service innovations. This research is based on qualitative research method with descriptive type. Data were collected through interviews, observation and documentation. The data validation technique uses the theory of Miles & Huberman. The results of the research show that the implementation of the South Sulawesi JIPP is well implemented, with the ability to distribute the latest information with the support of a website that was created, as a learning tool and a data center for public service innovation information, and become a center for accelerating the quality of public services in the province of South Sulawesi so that a number of Regional Apparatus Organizations have succeeded. won an award at the Public Service Innovation Competition at the National level. The Public Service Innovation Network is a stakeholder collaboration node for the success of the one agency one innovation movement so that ultimately a creative climate is created to create public service innovations in the scope.